Pengaruh Penambahan Sari Daun Kelor Terhadap Kadar Kalsium dan Sifat Sensoris Pada Susu Kenari - Rotulung, Jeanet Christina; Djarkasi, Gregoria S. S.; Taroreh, Mercy I. R. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
The aim of this study was to analyze the effect of moringa leaf extract on calcium content and evaluate the sensory properties of canarium milk. The research method used was a completely randomized design with five treatments: A (no moringa leaf extract), B (10% moringa leaf extract), C (10% moringa leaf extract), and D (30% moringa leaf extract), and E (addition of 40% moringa leaf extract), and each treatment was repeated three times. The results of the next study were analyzed using ANOVA, if it showed a real driver with a level of 5%, then the LSD test would be continued. The results showed that the calcium content of moringa canarium milk was 17.53 ppm – 535.12 ppm. Sensory properties using the liking level test, obtained the panelists' liking level for color ranging from 3.20 to 3.80 (neutral-like), aroma 2.94-3.64 (neutral-like), texture 3.16-3.68 (neutral-like), and taste 3.20-3.76 (neutral-like). The highest calcium levels were found in the treatment with the addition of 40% moringa leaf extract to canarium milk, and the sensory attributes of the color, aroma, texture, and taste of canarium milk after the addition of 40% moringa leaf extract were liked by the panelists.